It’s Been Said about “Her”. Gender Significance in the Biographic Discourses about Tita Merello (Revista Argentina de Musicología, 2021)
A movie about Tita Merello’s life, one of the most salient tango singers between the 1930s and 1960s, premiered in 2017. A “sensual heroine” and an artistic representation of popular Buenos Aires cabaret and nightlife women, Merello was an important actress from the Argentinean golden age of cinema valued more for her work in films and theater than for her place in popular music history (where she is often criticized for her vocal quality). In the context of the growing presence of gender and sex discourses on Argentinean society, the movie features a new type of biographical narrative about “La Merello” in which the present is assumed to be a better time for women than the past in reference to a singer like her, who was born in the brothel scene and became one of the most acclaimed feminine figures in the 20th-century Argentinean entertainment industry. This article analyzes and problematizes the biographic discourses fashioned about Tita Merello at different moments by a wide variety of biographers —from conceptual frameworks developed within the social sciences in conversation with popular music studies as well as gender and communication fields— in order to examine the current constructions of gender’s significance in the history of tango and tango singers.
Keywords: Biographic discourses; gender studies; tango; Tita Merello